Effectiveness of outpatient parenteral antimicrobial therapy (OPAT) for patients with cranial infection - Kilinc, Fatma; Setzer, Matthias; Behmanesh, Bedjan; Jussen, Daniel; Gessler, Florian; Bayerl, Simon; Kempf, Volkhard A. J.; Kessel, Johanna; Czabanka, Marcus; Prinz, Vincent (Frontiers in Medicine, 2023)
Outpatient parenteral antimicrobial therapy (OPAT) is a well-established and cost-effective method for improving the efficient use of healthcare resources. However, only a few centres in Germany perform it. Here we analysed OPAT for the treatment of patients with cranial infections in our neurosurgical department.This retrospective study analysed patients with cranial infections and the need for intravenous (i.v.) antimicrobial treatment between 2018 and 2021.All diagnosed intracranial infections were defined into two infection categories such as longterm antimicrobial treatment and short-term antimicrobial treatment. All included patients were discharged with a peripherally inserted central catheter (PICC) line. Prior to discharge, all patients received training in the safe administration of their medications via the PICC line. The duration of OPAT and the rate of readmission after OPAT were analysed.We identified a total of 45 patients treated with OPAT for cranial infections. Intradural involvement was present in 40 cases (88.9%). The average length of hospital stay for this cohort after surgical treatment was 45±15 days. 5 patients were treated for soft tissue/skin infection.Surgery was not required in this cohort. The mean hospital stay for this cohort was 8±6 days.Gram-positive organisms were isolated in most cases (53.3%). The most common pathogens were Staphylococcus aureus followed by other Staphylococcus species. For all included patients, OPAT was performed after discharge for an average of 43.1±14 days. There were five cases of readmission due to treatment failure. No serious adverse events or complications of OPAT were observed.OPAT enables better patient-centred healthcare close to home. The length of hospital stay can be reduced and adverse events due to prolonged hospitalisation can be avoided.